Consensus vs.evidence in medicine: resuscitation - Kloeck, Walter G.J. (SA Heart Journal, 2017)
Despite advances in medical education, equipment and facilities, survival rates following cardiac arrest over a 40-year period have not improved significantly. Attempts to scientifically review resuscitation techniques commenced in 1966, with the American Heart Association publishing recommended standards and guidelines in 1974, 1980 and 1986. In 1987, the Heart Foundation of South Africa convened a National CPR Symposium with a view to achieving national consensus guidelines for the teaching, training and performance of CPR. This was followed by the formation of a Southern African Resuscitation Council in 1989 in order to foster and co-ordinate the practice and teaching of resuscitation and to promote uniformity and standardization of resuscitation techniques. With the creation of Resuscitation Councils worldwide, an International Liaison Committee on Resuscitation (ILCOR) was established in 1992, comprising representatives from the American Heart Association, the Heart and Stroke Foundation of Canada, the European Resuscitation Council, the Australian Resuscitation Council and the Resuscitation Council of Southern Africa. ILCOR’s mission is to provide a consensus mechanism by which the international science and knowledge relevant to emergency cardiovascular care can be identified and reviewed. ILCOR has published more than 18 scientific Advisory Statements, including the 2000 and 2005 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science with Treatment Recommendations. A Universal Cardiac Arrest Algorithm was designed, reflecting major consensus recommendations placed in chronological sequence. Since the publication of the 2005 International Consensus, survival rates appear to be doubling or tripling worldwide.